COVİD-19 KISITLAMALARI SÜRECİNDE LİSANSÜSTÜ ÖĞRENCİLERİN ÇEVRİMİÇİ EĞİTİM DENEYİMLERİNİN İNCELENMESİ (İLAHİYAT VE İSLAMİ İLİMLER EĞİTİM PROGRAMLARI ÖRNEĞİ). - İPEK, Yasemin; ŞİMŞEK, Vahdeddin; Sözen, Hasan (International Anatolian Journal of Social Sciences / Uluslararasi Anadolu Sosyal Bilimler Dergisi, 2022)
It is applied of student’s opinions who continue their graduate programs on the online (online) education and training in the faculty of school of theology and Islamic sciences in this study. It is obtained data from the study and is used to determine the strengths and weaknesses of online theology/Islamic sciences graduate education, to explain the overall attitude levels of students to online learning, and to determine whether their overall attitude differs according to various variables. The study universe of the research is students who continued their postgraduate education programs in the field of theology/Islamic sciences of various universities during the spring semester of 2019-2020 and fall 2020- 2021 and experienced the online education process due to COVID-19 limitations. In the study, a mixed model is adopted as a research method. Screening for the quantitative dimension and case study for the qualitative dimension of the research are opted. A screening model from quantitative research methods has been preferred and as a data collection tool; the questioner containing questions related to personal information is used with the necessary permissions of the "Online Learning Attitude Scale" developed by Usta, Ilker and Okur (2016) containing survey questions to obtain students' opinions on online learning in the curriculum of graduate theology/Islamic sciences programs. It is used a questionnaire consisting of expressions in the form of students' special views to determine online theology/Islamic sciences programs by using some expression. This scale used in the research was applied to 200 students who continued their postgraduate education programs in the field of theology/Islamic sciences during the spring semester of 2019-2020 and fall 2020-2021 and experienced the online education process due to Covid-19 limitations. The reliability control of the scale was provided with the data obtained as a result of the application. Descriptive statistics were made in the SPSS package program to analyse the data obtained from the study group. In order to ensure that the findings obtained is supported by qualitative data, the examination quotation statements were included in the qualitative data obtained from the students. The results of the study has showed that the in the online education process perceptions of distance education of graduate students in theology and Islamic sciences differ according to gender, the willingness of instructor to use online education systems, the position of the university to their residence, the department in progress, and the internet connection status. It has been moreover found that students tend to view face-to-face education as more effective and preferable than online education. However, the scale of the findings from the survey findings and the findings from the qualitative data. They are considered it is understood to be done with more reasonable as a whole when statements; it is understood that the evaluations are made with a space-oriented approach to evaluations instead of general implications for graduate theology/ Islamic science programs. Accordingly, it is seen that it is even more meaningful which courses are more suitable for face-to-face, which one to run hybrid applications and which ones are more suitable for the online education model. Redesigning the online process within the scope of adult education, taking into account the changing roles of students again, can make a positive contribution. In addition, the need for interdisciplinary studies on the development of course materials appropriate to the online course processes for each discipline and the review of methods and techniques may be raised in order to make online graduate theology/Islamic sciences education processes more effective. They can on the other hand, gain more experience and experience related to distance learning programs through various seminars. Along with students, teachers can also develop a positive attitude towards distance education.